COVID-19 vaccine acceptance and hesitancy among the general population of Pakistan: a population-based survey. Issue 9 (17th September 2022) - Soomar, Salman Muhammad; Soomar, Sarmad Muhammad; Khan, Maria; Moin, Ghazal; Azam, Iqbal
Abstract : Objectives: This study aims to determine the COVID-19 vaccination coverage and the factors associated with vaccine acceptance and hesitancy in the general population of Pakistan. Setting: This population-based study covers all major areas of Pakistan, including Sindh, Punjab, Khyber Pakhtunkhwa and Baluchistan provinces and the capital Islamabad. Participants: A total of 541 male and female Pakistani adults above 18 years were interviewed to determine the COVID-19 vaccination coverage and understand the factors associated with vaccine acceptance and hesitancy. Outcome: The outcome was COVID-19 vaccination status (not vaccinated or vaccinated). Results: Of 541 participants, 227 (41.96%) were non-vaccinated and 314 (58.04%) were vaccinated. Two-thirds of the participants from both the non-vaccinated and vaccinated groups (185 (81.50%) vs 236 (75.16%), p=0.008) reside in Sindh. Nearly one-third of participants from both groups were ever infected with COVID-19 (77 (33.92%) and 90 (28.66%)). The odds of COVID-19 vaccination among the age group 34–42 years were 1.75 times higher (95% CI 1.35 to 2.09, p=0.008) than the other age groups. The odds of COVID-19 vaccination among those with COVID-19 ever-infected family members were 1.87 times higher (95% CI 1.56 to 2.34, p=0.032) than those with uninfected family members. Conclusions: Targeted interventions for subsets of populations reluctant to vaccination can improve vaccine coverage. Moreover, advocacy and explaining the public health benefits of vaccination can enhance the coverage in Pakistan.